2018
DOI: 10.7755/fb.116.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal maturation of the female smooth lumpsucker (Aptocyclus ventricosus)

Abstract: Abstract-Features of oogenesis, ovarian maturity phases, and fecundity of the smooth lumpsucker (Aptocyclus ventricosus) are described here for the first time. Gonadal development was examined by histological methods and the morphological features and size of germ cells at various stages was determined. These features were used to more accurately define morphological criteria of 7 histological and macroscopic maturity phases. The smooth lumpsucker is an iteroparous gonochoristic species with determinate fecund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Size-frequency analyses of oocytes revealed discontinuous oogenesis (determinate fecundity), group-synchronous ovarian organization (release of eggs once in the spawning season), and total spawning, following the classification of Murua and Saborido-Rey (2003). Similar reproductive strategies have been recorded for other representatives of Cyclopteridae, such as the smooth lumpsucker (Zhukova et al, 2018).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Size-frequency analyses of oocytes revealed discontinuous oogenesis (determinate fecundity), group-synchronous ovarian organization (release of eggs once in the spawning season), and total spawning, following the classification of Murua and Saborido-Rey (2003). Similar reproductive strategies have been recorded for other representatives of Cyclopteridae, such as the smooth lumpsucker (Zhukova et al, 2018).…”
Section: Discussionsupporting
confidence: 56%
“…It is difficult, therefore, to determine if lumpsucker species feed during their entire life cycles. However, other representatives of Cyclopteridae, the Atlantic spiny lumpsucker, smooth lumpsucker, and lumpfish, can spawn several times during their life cycles (Cox and Anderson, 1922;Berge and Nahrgang, 2013;Zhukova et al, 2018).…”
Section: Fishery Bulletinmentioning
confidence: 99%
See 1 more Smart Citation
“…, Zhukova et al. ), which makes them accessible to AFSSLs in shallow waters and may account for the limited variation in diving behaviors observed across seasons. Although our results were inconsistent with studies that indicated maximum dive depths of wDPS AFSSLs during winter were greater than during summer (Merrick et al.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, Pacific cod are most abundant on the continental shelf and tend to exhibit site fidelity (Bakkala 1984, possibly rendering them predictable prey for AFSSLs as well. During this time of year, smooth lumpsuckers also migrate from deep waters to nearshore areas to spawn at depths <10 m (Mecklenburg et al 2002, Zhukova et al 2018, which makes them accessible to AFSSLs in shallow waters and may account for the limited variation in diving behaviors observed across seasons. Although our results were inconsistent with studies that indicated maximum dive depths of wDPS AFSSLs during winter were greater than during summer (Merrick et al 1994, Merrick andLoughlin 1997), it is important to emphasize that seasons were not defined consistently across studies.…”
Section: Western Alaska Afssls (Western Dps)mentioning
confidence: 99%